Association between the Dietary Index for Gut Microbiota and periodontitis: mediation by systemic inflammation - Zhu, J. H.; Sun, Gehong; Guo, Jia; Li, Yongjuan; Jing, Yichao; Zhang, Zhen; Pan, Wenting (Frontiers in Nutrition, 2025)
ObjectiveThis study aimed to explore the association between the Dietary Index for Gut Microbiota (DI-GM) and periodontitis, and to investigate the mediating role of systemic inflammation in this relationship.MethodsWe performed a cross-sectional analysis using data from the National Health and Nutrition Examination Survey (NHANES) 2009–2014, including 9,022 participants. DI-GM scores were derived from 14 dietary components known to influence gut microbiota. Periodontitis was defined using a reduced version of the Centers for Disease Control and Prevention and American Academy of Periodontology criteria. Multivariable logistic regression and restricted cubic spline (RCS) analyses were employed to assess the association between DI-GM and periodontitis. Additionally, mediation analysis was performed to examine the contribution of systemic inflammation biomarkers to the observed associations.ResultsHigher DI-GM scores were inversely associated with periodontitis prevalence, with each 1-point increase in DI-GM reducing the odds of periodontitis by 5% (95% CI: 0.92–0.97; p < 0.001). Participants in the highest DI-GM group had 19 and 26% lower odds of moderate and severe periodontitis, respectively, compared with the lowest group. Mediation analysis suggested modest mediation effects for systemic inflammation biomarkers, particularly CRP (8.1%) and WBC (5.5%), indicating that systemic inflammation may partially explain the observed associations.ConclusionOur findings indicate that greater adherence to DI-GM is associated with lower periodontitis prevalence, partly mediated by systemic inflammation, highlighting dietary modulation of gut microbiota as a potential strategy for periodontal disease prevention.